2021
DOI: 10.1021/acs.jmedchem.1c00996
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis-Targeting Chimera (PROTAC) Modification of Dovitinib Enhances the Antiproliferative Effect against FLT3-ITD-Positive Acute Myeloid Leukemia Cells

Abstract: Acute myeloid leukemia (AML) refers to one of the most lethal blood malignancies worldwide. FLT3-ITD mutation is recognized as the most common one that predicted a poorer prognosis. There have been many prominent FLT3-ITD inhibitors approved by the FDA for clinical therapies. However, as impacted by undesirable off-target effects, differentiated metabolic issues, and clinical drug resistance problems, it remains challenging to discover alternative and promising solutions for treating FLT3-ITD+ AML. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It has been found that 753B effectively eliminates AML cells and enhances the efficacy of chemotherapy by targeting senescent cells; this study also confirmed recent findings that standard chemotherapy with cytosine arabinose (Ara-C) induced cellular senescence (SnCs) in AML cells, manifested by increased cell size, the induction of senescence-associated β-galactosidase activity, the upregulation of cell cycle regulator proteins (p16, p21, p53), and the expression of the senescence-associated secretory phenotype factors (IL-6, IL-18, IL-1β), leading to chemoresistance in AML [ 89 ]. 753B has been found to reverse chemotherapy-induced SnCs phenotype and induce death in senescent AML cells by increasing BCL-XL/BCL-2 expression, and to trigger time and dose-dependent BCL-XL degradation at concentrations lower than that of DT2216 [ 90 , 91 ]. 753B also showed potency in nine venetoclax-resistant samples, of which six demonstrated BCL-2 degradation [ 88 , 92 ].…”
Section: In the Grip Of Apoptosis—the Desired Future After Venetoclaxmentioning
confidence: 99%
“…It has been found that 753B effectively eliminates AML cells and enhances the efficacy of chemotherapy by targeting senescent cells; this study also confirmed recent findings that standard chemotherapy with cytosine arabinose (Ara-C) induced cellular senescence (SnCs) in AML cells, manifested by increased cell size, the induction of senescence-associated β-galactosidase activity, the upregulation of cell cycle regulator proteins (p16, p21, p53), and the expression of the senescence-associated secretory phenotype factors (IL-6, IL-18, IL-1β), leading to chemoresistance in AML [ 89 ]. 753B has been found to reverse chemotherapy-induced SnCs phenotype and induce death in senescent AML cells by increasing BCL-XL/BCL-2 expression, and to trigger time and dose-dependent BCL-XL degradation at concentrations lower than that of DT2216 [ 90 , 91 ]. 753B also showed potency in nine venetoclax-resistant samples, of which six demonstrated BCL-2 degradation [ 88 , 92 ].…”
Section: In the Grip Of Apoptosis—the Desired Future After Venetoclaxmentioning
confidence: 99%
“…In 2021, Yang group obtained a series of PROTACs based on the binding model of Dovitinib and FLT3. 169 After screening in vitro antiproliferative activity, it was found that the degrader 101 (Fig. 24 ) and 102 (Fig.…”
Section: Protacs Targeting Cancer-related Targetsmentioning
confidence: 99%
“…Small molecule inhibitors (particularly tyrosine kinase inhibitors) proved a great breakthrough in increasing survival rates amongst Leukemia patients (Burslem et al, 2019). However, drug resistance, life-long use and chances of relapse pose serious concerns (Mahon et al, 2010;Corbin et al, 2011;Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%